Hybrid Single-Stage Repair of Kommerell's Diverticulum in a Right Aortic Arch in a Patient With 22q11.2 Deletion Syndrome. (August 2022) - Chourda, Emmanouela; Putotto, Carolina; Versacci, Paolo; Saltarocchi, Sara; D'Abramo, Mizar; Tshomba, Yamume; Tinelli, Giovanni; Miraldi, Fabio
Hybrid single-stage repair of Kommerell's diverticulum in a right aortic arch. Aortic arch anomalies, isolated or associated with congenital heart defects, are cardiovascular manifestations frequently associated with 22q11.2 deletion syndrome. Kommerell's diverticulum in the context of a right aortic arch is an exceedingly rare congenital anomaly, consisting in aneurysmal degeneration of the origin of an aberrant left subclavian artery. Open surgical repair has been the treatment paradigm, but in recent years, hybrid and endovascular procedures have also been proposed. In this report we present the case of a patient affected by 22q11.2 deletion syndrome successfully treated for Kommerell's diverticulum associated with a right-sided aortic arch through a single-stage hybrid procedure, consisting of bilateral carotid-subclavian bypass, exclusion of the diverticulum by an endovascular thoracic stent graft, and aberrant left subclavian artery plug occlusion. This type of hybrid technique can be an excellent alternative to extensive open surgical repairs or when total endovascular repair is deemed unachievable, also in the context of a complex genetic syndrome.